Aproveitamento da informação tecnológica em pesquisas acadêmicas: análise de citações de patentes em teses e dissertações da área de engenharia - Camargo, Juliana Ravaschio Franco de (2011)
It is believed that patents are not fully explored as documents that supply technological information, among companies, and by research institutions, universities, etc. In this context, this descriptive, quantitative and documental research aimed to check if the engineering students of the University of Campinas, Brazil (UNICAMP) use patents as information sources in their academic researches. Five faculties were considered for this study: Chemical Engineering Faculty (FEQ), Mechanical Engineering Faculty (FEM), Faculty of Electrical Engineering and Computing (FEEC), Agricultural Engineering Faculty (FEAGRI) and Faculty of Civil Engineering and Architecture (FEC). Thus, the sample comprises 3045 dissertations and doctoral theses of the mentioned faculties, from 2000 to 2007. The data were collected through patents cited and referenced in academic papers, and to facilitate this process there was an attempt to automation using Adobe Acrobat Professional. It was concluded that patents are not widely used as sources of information in dissertations and doctoral theses by the Unicamp s students of engineering. In most of the items analyzed patents do not represent even 5% of the documents quoted. Moreover, it was not possible to realize a growth of quotations of this kind of document over the years, but only oscillations from one year to another. Regarding the use of patents by the five faculties studied, it was found that FEQ stood out compared with the others in this matter, with 3.15% works that have used patents in their citations. Following results are: FEM with 1.61%, FEEC with 1.25%, FEAGRI with 0.20%, and finally FEC with 0.16% citations. Although students of a particular faculty have cited more patents than others, it is evident that they do not make the most of this kind of document as information source. Also, it was not observed important differences in the use of patents from one faculty to another. Finally, it was found that the Engineering faculty, which produces and deposits more patents at the University is not the one that uses it at most as a source of information.